Лекции по дифференциальным уравнениям: учебное пособие - Имас О. Н. Ольга Николаевна; Пахомова Е. Г. Елена Григорьевна; Рожкова С. В. Светлана Владимировна; Устинова И. Г. Ирина Георгиевна (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана